THE ACCULTURATION OF GLOBALIZATION: A Case Study of Liberia - Okorieoji Matthew C (Graduate School of International Studies Ajou University, 2014)
ABSTRACT With Globalization being the grand issue of this age, it seems to me a lot need to be fathomed of it, if it is to do more good than harm to the greater portion of the world’s population especially the majority of citizens of developing and least developed countries both at private and public levels. Though I am aware that many scholars have either defined or explained globalization in many ways and from varying perspectives yet it has remained a mysterious phenomenon that still require further diligent and prudent investigation. Therefore, since most existing or current explanations are not clear enough to provide us with better insight on what globalization is and how it affects the poor, it is expedient that ways and means be invented on how both individuals and nations can rightfully position themselves for a ‘win-win’ in this global game or else find themselves losers in this ever fascinating global system. Additionally, this research will look at the inclusion, informalization and the capitalization of the informal economic sector that holds the greater share of the assets needed to resurrect and accelerate the Liberia economy and even that of other developing countries alike, with a resultant effect in the acceleration of both their individual and national economy. Also this research will explore the helpfulness of development assistance to Liberia if properly managed, by both the state and the citizens, by appropriately directing the funds to their various intended projects and programs combined with citizens’ participation. It will also look at some international laws and regimes, such as the Washington Consensus and how it impasses economic development in the developing countries, the West’s easy access into the developing countries but mountainous barricades for the citizens of the developing countries in accessing the Western market and other forms of discrimination against the developing countries citizens by the developed and others alike.
학위논문(석사)--아주대학교 Graduate School of International Studies :NGO학과,2014. 8